Charms of the Cynical Reason Tricksters in Soviet and Post-Soviet Culture - Lipovetsky, Mark (Cultural Revolutions: Russia in the Twentieth Century, 2016)
Frontmatter -- TABLE OF CONTENTS -- Acknowledgements -- INTRODUCTION -- 1. AT THE HEART OF SOVIET CIVILIZATION -- 2. KHULIO KHURENITO : THE TRICKSTER'S REVOLUTION -- 3. OSTAP BENDER: THE KING IS BORN -- 4. BURATINO : THE UTOPIA OF A FREE MARIONETTE -- 5. VENICHKA: A TRAGIC TRICKSTER -- 6. TRICKSTERS IN DISGUISE: THE TRICKSTER'S TRANSFORMATION S IN THE SOVIET FILM OF THE 1960s-70s -- 7. SPLITTING THE TRICKSTER: PELEVIN'S SHAPE-SHIFTERS -- CONCLUSION -- WORKS CITED -- INDEX